Pengaruh Kesehatan dan Keselamatan Kerja (K3) dan Lingkungan Kerja Terhadap Kinerja Melalui Kepuasan Kerja Pegawai pada PT. PLN (Persero) ULP Melak - Amrullah Febrian; Nurhidayati (Economic Reviews Journal, 2025)
Implementing occupational health and safety in a good working environment creates a safe, comfortable and accident-free workplace. The concept of occupational health and safety ensures every employee a safe and positive working environment, but this idea is not yet fully understood by management and staff. This research aims to assess how occupational safety and health, working environment conditions and employee satisfaction influence performance This study uses partial least squares analysis and combines external and internal model evaluations, drawing on a group of 97 participants. The results show that job security and work environment have an impact on performance. Although job security and working conditions affect performance, job satisfaction does not. In contrast, both job security and work environment have an indirect impact on performance via job satisfaction.